Nutrient Status among Latvian Children with Phenylketonuria - Olga Lubina; Linda Gailite; Julija Borodulina; Madara Auzenbaha (MDPI AG, 2023)
(1) Introduction: Phenylketonuria (PKU) is an autosomal recessive inborn error of phenylalanine metabolism. The main treatment for PKU is to manage nutrition, thereby restricting phenylalanine intake. Part of patient management is analyzing eating habits to substitute missing nutrients and limit the overdose of nutrients. This is mainly done by analyzing food diaries. This is the first review of Latvian PKU patients eating habits performed by analyzing 72-h food diaries (FD). (2) Materials and Methods: This study included individuals between the ages of 18 and 31 years, PKU patients and 31 age- and sex-matched control groups. All respondents kept 72-h food diaries (FD) and underwent testing for zinc, selenium and ferritin levels in the blood. Food diary data were analyzed by Nutritics software to calculate the theoretical intake of nutrients, and these values were compared with the Ministry of Health of the Republic of Latvia's recommended values. (3) Results: A lack of motivation and diet therapy compliance in PKU patients was observed during this research. A total of 32% of PKU patients refused to fill out their FD or filled it out incorrectly. The analysis of nutrient intake was observed, and there was a statistically significant difference between PKU patients in the 1-3 age group and the control group in fat intake. Fat intake in PKU patients was below MRHL recommendations. The intake of iron was found to be surplus in all PKU patients in the age group of 1-3, 91% of PKU patients in the age group of 4-6 years, 63% in the age group of 7-12 and 71% in the 13-18 year age group. Although there were no instances in the PKU patients nor the control group who had ferritin levels above the normal range. Selenium intake was surplus in 80% of PKU patients in the 1-3 age group, 91% in PKU patients in the 4-6 age group, 88% in the 7-12 age group and 86% in the 13-18 age group. None of the patients had Se levels in the blood above the normal range. Zn intake was surplus in 100% of PKU patients in the 1-3 age group, 82% in PKU patients in the 4-6 age group, 88% in the 7-12 age group and 57% in the 13-18 age group, and no PKU patients had high Zn levels. None of the control group participants had levels below the normal range of Zn and Se while 11% of PKU patients in the 13-18 age group had inadequate levels of Se, although Se intake based on their FD was optimal. (4) Conclusions: Regular PKU patient nutritional status evaluation is important to define and prevent possible nutrient deficiency, and further investigation should be continued to find out the mechanism of nutrient absorption in PKU patients. To prevent macronutrient deficiency such as fat and micronutrient deficiency in PKU patients, one could use supplements or try an improved nutrient content of Phe-free formula in the future.